Predisposing Factors and Treatment Outcome of Otomycosis - ., Arifullah; Hassan, Syed Zafar; Din, Israr -Ud- (Journal of Gandhara Medical and Dental Science, 2016)
OBJECTIVES: The aim of this study was to determine the predisposing factors and treatment outcomes of otomycosis. METHODS: This was an observational study conducted from July 2008 to August 2012 at ENT department of Khyber Teaching Hospital, Peshawar. Total of 110 patients of all age and both sexes were selected from OPD for the study, using convenient sampling. The predisposing factors and treatment outcome of otomycosis were observed. Results were recorded in percentages. RESULTS: In our study we documented 110 patients having otomycosis. There were 57.3% (63/110) males and 42.7% (47/110) females. Patients ranged from 21 to 40 years were more affected. Mean follow up time was 2 years. The most common predisposing factors were swimming in 49.1% (54/110) patients followed by topical antibiotic drops, cerumen, immune-compromised status and hearing aid use. The most common presenting symptom was otalgia and itching ear in almost every patient 100% (110/110), followed by hearing loss and ear discharge. In our study 1% clotrimazole drops or lotion was applied to all patients after cleaning the fungus debris and cleansing the ear with acetic acid. The treatment outcome was resolution in 57.3%, residual 24.5% and recurrence 12.7%. 5.5% of patients did not come for follow up. The complications were TM perforation in 13.6% patients, serous otitis media in 3.6% and external auditory canal osteitis in 0.9%. CONCLUSION: Otomycosisis usually resolves with local toilet of ear and instillation of antifungal agents, however eradication of disease is difficult in presence of a mastoid cavity and immune-compromised patients.